2015
DOI: 10.1007/978-3-319-06086-6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Stress Analysis for Materials and Structures

Abstract: The first € price and the £ and $ price are net prices, subject to local VAT. Prices indicated with * include VAT for books; the €(D) includes 7% for Germany, the €(A) includes 10% for Austria. Prices indicated with ** include VAT for electronic products; 19% for Germany, 20% for Austria. All prices exclusive of carriage charges. Prices and other details are subject to change without notice. All errors and omissions excepted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 0 publications
0
27
0
1
Order By: Relevance
“…This is an example of a quite conventional load cell, where strain gage locations and connections are suitably chosen to prevent any coupling or secondary effect. The effect is an excellent decoupling, as testified by the diagonal layout of the matrix C and the low values of the related coupling coefficients C.C.s 23 …”
Section: A Load Cell For the Simultaneous Measurement Of Two Forces Amentioning
confidence: 97%
See 4 more Smart Citations
“…This is an example of a quite conventional load cell, where strain gage locations and connections are suitably chosen to prevent any coupling or secondary effect. The effect is an excellent decoupling, as testified by the diagonal layout of the matrix C and the low values of the related coupling coefficients C.C.s 23 …”
Section: A Load Cell For the Simultaneous Measurement Of Two Forces Amentioning
confidence: 97%
“…Each trial was repeated three times for statistical evidence reasons. 7,22,23 Some photos of the loading trials are shown in Fig. 4.…”
Section: A Load Cell For the Simultaneous Measurement Of Three Forcesmentioning
confidence: 99%
See 3 more Smart Citations